BLENDED LEARNING THE IMPLEMENTATION OF ROTATION ORIENTED BLENDED LEARNING MODEL IN THE NEW NORMAL ERA COVID 19 - Hamela Sari Sitompul; Idawati Situmorang (Sean Institute, 2021)
To improve the quality of education in facing the future, it is necessary to change the learning paradigm through shifting the procedures for organizing educational and learning activities. Moreover, the spread of the virus in Indonesia which was dangerous and had previously been felt by the whole world before 2020, namely the Corona Virus Diseased 2019 or known as COVID-19 made the learning process hampered. These conditions make the learning system that was originally face-to-face in class must be adapted to learning at home. This study aims to implement a two-way communication-oriented Blended Learning model in the new normal era of covid 2019. However, this learning model is adjusted to the conditions in the school area where the research is carried out. The trial was conducted on 36 students of class XI SMA Yapim Taruna Dolok Masihul. Student learning outcomes were measured using various instruments. Assessment of student knowledge is carried out using multiple-choice tests; assessment of student skills is measured using portfolio assessment, while attitude assessment is measured using questionnaires. The results of this study indicate that the implementation of the Blended Learning learning model is able to improve student learning and learning outcomes. This can be seen from the learning activities of students in the class whose data was taken based on a questionnaire in the first cycle in the good category of 58.33% and in the second cycle it increased to 63.89% in the good category and 16.67% in the very good category. The increase in student learning activities was followed by an increase in student mastery of learning as shown in the posttest results at the end of the cycle. In the first cycle, the number of students who scored 70 was 25 students or 69.44%. In the second cycle, there was an increase of 24.45%, namely 88.89% or as many as 32 students who had obtained a score of 70.